Disease prevalence and clinicopathological changes in senior and geriatric cats presented to University Veterinary Hospital, Universiti Putra Malaysia - Lim, May Lyn; Abdullah, Rasedee; Dhaliwal, Gurmeet Kaur; Omar, Mohamed Ariff (2012)
This retrospective study reports on the prevalence of disease, clinicopathological changes and diagnosis in senior and geriatric cats presented to University Veterinary Hospital (UVH), Universiti Putra Malaysia between 2009 and 2011. The age distribution of cats presented to UVH, level of preventive health care and cost of treatment per cat per annum were also determined. The majority of the feline patients were less than 3 years old. Senior and geriatric cats made up 1.4% of all cats in the study. Kidney disease, dental disease, neoplasia and feline upper respiratory tract disease were the most commonly reported disorders in senior and geriatric cats. Furthermore, blood lymphocytes count and albumin level were significantly lower in older cats compared to adult as a result of immuno-senescence and age-related physiological changes. Preventive care was poor for senior and geriatric cats, with only 9% presented for wellness examination. In general, cost of veterinary care was significantly lower for those that received preventive health care than those that did not. The results from this study can be used by veterinary practitioners to better understand, anticipate health problems of senior and geriatric cats and to encourage clients to subscribe to a semi-annual wellness programme for their older cats.